Classroom discourse and disability: Interactional opportunities for development of self-determination beliefs. Issue 1 (2nd January 2021) - Louick, Rebecca; Wang, Min
Abstract: This qualitative study of ongoing interactions in a high school classroom illustrates how teachers' specific interactive choices can provide crucial opportunities for students with disabilities to develop feelings of self-determination. Classroom video data, collected throughout a multi-week writing assignment, were analyzed using a discourse analytic approach, focusing on how student and teacher used linguistic resources (such as personal pronouns and modal verbs), as well as how they co-constructed the context for learning. Findings enabled greater understanding of the ways in which participants negotiated issues of power, role, and responsibility over the course of an academic project. The relationships built in this particular special education learning environment supported the focus student in seeing learning supports and strategies as acceptable, useful, and desirable; these relationships also allowed him opportunities to develop the self-regulatory skills and feelings of relatedness critical to strong self-determination beliefs.